Segodniashnii den' Moldovy . Segodniashnii den' Moldovy . Today in Moldova . Сегодняшний день Молдовы - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Agrarian reform; work at the "Electromash" factory in Tiraspol and the "Alfa" factory in Chisinau. Featured in the program: Snegur, Mircea (President of Moldova) Contributors: Chibotaru, Lilian (Anchor) Земельная реформа; работа завода "Электромаш в г. Тирасполь и завода "Альфа" в Кишиневе. В программе участвуют: Снегур, Мирча (Президент Молдовы) Создатели: Чиботару, Лилиан (Ведущий/Ведущая)